Experimental Investigation of Concrete-Infilled Bamboo for Structural Performance in Compression for Low-Cost Building - Sam Bulolo; James Gowon Okuda; Michael Kyakula (Advances in Civil Engineering)
The study explored an innovative scheme to improve the load-bearing capacity of bamboo by infilling it with concrete to form a composite column as a compression member for low-cost buildings. A total of four samples of bamboo of five different lengths (0.2, 0.4, 0.6, 0.8, and 1 m) were prepared with concrete (concrete infilled) and without concrete for three different commonly used concrete grades (C12/15, C15/20, and C20/25) and the load-carrying capacity tested to determine its resistance under compression. Generally, there was a considerable improvement in structural performance in terms of load-carrying capacity when the bamboo culms were infilled with plain concrete. The failure load capacity of plain bamboo (no concrete infill) was reduced by 26.4% with an increase in the length of the bamboo from 0.2 to 1 m. Concrete-infilled bamboo with C15, C20, and C25 led to an increment of 58.7%, 103%, and 139.1% of the failure load capacity relative to that of the plane bamboo culms sample test length at 1 m, respectively. Bamboo infilled with concrete grade C25 had a larger failure load as compared to those infilled with concrete grade C20 and C15. The study concludes that concrete in-filled bamboo increases the buckling resistance as well as the load-carrying capacity and it can be an alternative composite building material to steel and concrete for building under light loads.